The BCOR-rearranged sarcoma involving the lung: Diagnosis with clinical outcome and literature review - Rakesh K. Gupta; Bharat Rekhi; Mehar C. Sharma; Ranganath Ganga; Mudalsha Ravina; Amit Kumar; Dibakar Sahu (Indian Journal of Pathology and Microbiology)
BCOR-rearranged sarcomas (BRS) constitute relatively newly described sarcomas, which, within the musculoskeletal sites, usually occur in the bones, followed by soft tissues. Primary BRS involving the visceral organs is very rare, and only a single case is reported in the lung. These tumors share overlapping morphological and immunohistochemical (IHC) features with other neoplasms, such as synovial sarcoma, Ewing sarcoma, as well as carcinosarcoma, the latter especially when occurring in the visceral organs. BCOR immunostaining is useful in triaging a tumor for molecular diagnosis, which constitutes the “essential” diagnostic criterion for these tumors. To report an extremely rare case of a BRS, confirmed by BCOR-rearrangement by fluorescence in situ hybridization (FISH), primarily occurring in the lung, emphasizing the diagnostic approach and management, along with review of literature. An18-year-old boy presented with complaints of left-sided chest pain, along with cough, fever, loss of appetite, and weight. On radio imaging, there was a complete collapse of the left lower lobe of lung with moderate pleural effusion. The biopsy showed a biphasic tumor comprising primitive round cells admixed with spindle cells. Immunohistochemically, the tumor cells were positive for BCOR, TLE1, and p53. FISH showed BCOR gene rearrangement. A diagnosis of primary BRS of lung was offered. The patient had a favorable response to the chemotherapy regime. BRS is an ultra-rare tumor, which rarely involves visceral organs. The lung is an exceptionally rare site, with only single reported case previously. An exact confirmation by molecular testing has treatment-associated implications. A review of similar reported cases is presented herewith.